Dynamic downscaling of the ERA-40 data using a mesoscale meteorological model - PAPADOPOULOS, A.; KORRES, G.; KATSAFADOS, P.; BALLAS, D.; PERIVOLIOTIS, L.; NITTIS, K. (Mediterranean Marine Science, 2011)
A sophisticated downscaling procedure that was applied to reproduce high resolution historical records of the atmospheric conditions across the Mediterranean region is presented in this paper. This was accomplished by the dynamical downscaling of the European Center for Medium-Range Forecasts ERA-40 reanalyses with the aid of the atmospheric model of the POSEIDON weather forecasting system. The full three dimensional atmospheric fields with 6 hours of temporal resolution and the surface meteorological parameters at hourly intervals were produced for a 10-year period (1995-2004). The meteorological variables are readily available at 10 km resolution and may constitute the atmospheric forcing to drive wave, ocean hydrodynamic and hydrological models, as well as the baseline data for environmental impact assessment studies. A brief overview of the procedure and a quantitative estimation of the benefit of the new dynamical downscaling dataset are presented.